"Giant" colloidal quantum well heterostructures of CdSe@CdS core@shell nanoplatelets from 9.5 to 17.5 monolayers in thickness enabling ultra-high gain lasing - Isik, Furkan (2024)
Semiconductor colloidal quantum wells (CQWs) have emerged as a promising class of gain materials to be used in colloidal lasers. Although low gain thresholds are achieved, the required high gain coefficient levels are barely met for the applications of electrically-driven lasers which entails a very thin gain matrix to avoid charge injection limitations. Here, "giant" CdSe@CdS colloidal quantum well heterostructures of 9.5 to 17.5 monolayers (ML) in total with corresponding vertical thickness from 3.0 to 5.8 nm that enable record optical gain is shown. These CQWs achieve ultra-high material gain coefficients up to ≈140 000 cm-1 , obtained by systematic variable stripe length (VSL) measurements and independently validated by transient absorption (TA) measurements, owing to their high number of states. This exceptional gain capacity is an order of magnitude higher than the best levels reported for the colloidal quantum dots. From the dispersion of these quantum wells, low threshold amplified spontaneous emission in water providing an excellent platform for optofluidic lasers is demonstrated. Also, employing these giant quantum wells, whispering gallery mode (WGM) lasing with an ultra-low threshold of 8 µJ cm-2 is demonstrated. These findings indicate that giant CQWs offer an exceptional platform for colloidal thin-film lasers and in-solution lasing applications.